Ceft-to-Ceft Study: Real-Life Experience with Ceftaroline and Ceftobiprole in Treatment of the Principal Infectious Syndromes in a Spanish Multicenter Hospital Cohort - Daniel Arnés García; Inés Pitto-Robles; Jorge Calderón Parra; Marina Calvo Salvador; Carmen Herrero Rodríguez; Laura Gisbert; Carmen Hidalgo-Tenorio (MDPI AG, 2023)
Background: To compare the real-life effectiveness and safety of ceftaroline fosamil (ceftaroline-F) and ceftobiprole medocaril (ceftobiprole-M) for infections in hospitalized patients. Methods: This comparative, observational, retrospective, and multicenter Spanish study included patients receiving outpatient parenteral antimicrobial therapy (OPAT) and hospitalized patients treated for at least 48 h with ceftaroline-F or ceftobiprole-M between their first incorporation in the clinical protocol of each hospital and 31 July 2022. Results: Ceftaroline-F was administered to 227 patients and ceftobiprole-M to 212. In comparison to the latter, ceftaroline-F-treated participants were younger (63.02 vs. 66.40 years, OR 1.1; 95%CI: 1.001-1.05) and had higher rates of septic shock (OR 0.27; 95%CI: 0.09-0.81) and higher frequencies of targeted (57.7 vs. 29.7%; OR: 0.35; 95%CI: 0.18-0.69) and combined (89.0 vs. 45.8%, OR: 0.13; 95%CI: 0.06-0.28) therapies that were second line or more (82.4% vs. 64.6%%; OR 0.35; 95%CI: 0.18-0.69), and higher rates of infections due to Gram-positive cocci (92.7 vs. 64.7%, p = 0.001), bacteremia (51.9 vs. 21.7%, p = 0.001), infective endocarditis (24.2 vs. 2.4%, p = 0.0001), and mechanical ventilation-associated pneumonia (8.8 vs. 2.4%, p = 0.0001). Ceftobiprole-M was more frequently administered against polymicrobial infections (38.1 vs. 14.0%, p = 0.001), those produced by Gram-negative bacilli (19.7 vs. 6.0%, p = 0.0001), nosocomial pneumonia (33 vs. 10.6%, p = 0.0001), and skin and soft-tissue infections (25.4 vs. 10.1%, p = 0.0001). Patients treated with ceftaroline-F had a longer hospital stay (36 (IQR: 19-60) vs. 19.50 (IQR: 12-30.75, p = 0.0001) days), with no difference in infection-related mortality at 14 (13.2 vs. 8.0%, p = 0.078) or 28 (4.8 vs. 3.3%, p = 0.415) days or in dropout rate for adverse effects (2.2 vs. 0.9%; p = 1). Conclusions: The fifth-generation cephalosporins, ceftaroline-F and ceftobiprole-M, are safe and effective in real life, with no difference between them in health outcomes.